(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
When used to an electric vehicle (EV), a high-speed motor is a practical means of achieving motor reduction. Since the rotor construction of a switched reluctance motor (SRM) is both simple and sturdy, this kind of motor may be used for highvelocity drives. The driving concept is effective, although it causes significant vibration and noise. Torque controllers are notoriously difficult to build because of the complexity introduced by traditional methods of current excitation. It has been suggested that SRM drive may benefit from the fuzzy with vector control in order to get over these issues. In the high-speed drive, vector control has not yet been implemented on the SRM. In this article, fuzzy control is used to clarify the optimal drive conditions—including switching frequency and bus voltage—for operating the SRM in the high-speed range. Fuzzy with vector control is proven to be able to drive the proposed SRM in the high-speed area, allowing for minimum vibration to be achieved.